Construction of Solar Cabinet Dryer for Technology Management of Processed Snakehead Fish Production - Klabprasitti, Anuchit; Supawantanakul, Dusanee; Sittisaungand, Prasoot; Sangsirimongkolying, Ratsamee (Princess of Naradhiwas University Journal, 2019)
The purpose of this research was to create a solar cabinet dryer for production of processed snakehead fish. The mixed research method and synthesized data was used to create a solar cabinet dryer. The population was 10 community enterprise of housewives whose processed snakehead fish production at Bang Phutsa sub-district, Mueang Sing Buri District, Sing Buri Province. The solar cabinet dryer was designed using solar cabinet dryer principle and ergonomic principle. The results found that the appropriate solar cabinet dryer was made from the light weight anodized aluminum with 120x120x120 cm3. The material was easy available in the community. It had wheels for convenience moving. It comprised of layer that easy to take off, cleaning, and maintenance. The temperature in solar cabinet dryer was higher than those outside the cabinet 10 – 12 °C. The maximum sunlight time gave 40-55 °C all over the cabinet. It could contain 60 fishes and 250-350 g each. The drying time was reduced for 2 hours. The moisture content of dried fish decreased for 27 (wb). This solar cabinet dryer was exhibited in One Tambon One Product of Sing Buri Province.